Negative electrode material and preparation method thereof, electrochemical device and electronic device

By regulating the pore structure of the graphite surface and doped metal elements of the negative electrode material, the problem of taking into account the fast charging performance and cycle life of lithium-ion batteries is solved, and higher dynamic performance and longer cycle life are achieved.

CN119674041AActive Publication Date: 2025-03-21NINGDE AMPEREX TECHNOLOGY LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411997002.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-21
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing lithium-ion batteries are difficult to have both fast charging performance and cycle life. Conventional modification processes can increase the charging rate while causing unstable interfaces during the cycle.

Method used

By regulating the number of pores on the graphite surface of the negative electrode material and the diameter of the pores, and doping metal elements such as Fe, Co, Ni, Cr, and Mn, a uniformly sized pore structure is formed to improve the uniformity of lithium ion deposition and transmission efficiency.

Benefits of technology

It has achieved the improvement of the room temperature kinetics of the negative electrode material and the fast charging anti-lithium-resolution capability, extended the cycle life of the lithium-ion battery, and improved the dynamic performance of the electrochemical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674041A_ABST
    Figure CN119674041A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material and a preparation method thereof, an electrochemical device and an electronic device, the negative electrode material comprises graphite, holes are formed in the surface of the graphite, the number of the holes is 20-2000 in a circular area with the diameter of 1 [mu] m on the surface of the graphite, and the average diameter of the holes is 10-100 nm; the negative electrode material contains metal elements, and the metal elements comprise at least one of Fe, Co, Ni, Cr and Mn. The negative electrode material provided by the invention can improve the charging rate and the cycle life of the electrochemical device at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical energy storage, and in particular to a negative electrode material and a preparation method thereof, an electrochemical device using the negative electrode material, and an electronic device using the electrochemical device. Background Art

[0002] As lithium-ion batteries are widely used in various fields, people's demands for fast charging performance and cycle life are becoming more and more stringent. In the 3C digital field, the fast charging performance and long cycle life of lithium-ion batteries are often not achieved at the same time. Usually, the charging rate can be increased through coating, modification and process adjustment, but at the same time it will bring about an unstable interface during the cycle. Therefore, it is necessary to develop a new modification process that can effectively improve the room temperature kinetics and fast charging resistance to lithium precipitation of the negative electrode material, while also improving the cycle life of lithium-ion batteries. Summary of the invention

[0003] The present application provides a negative electrode material and a preparation method thereof, an electrochemical device and an electronic device.

[0004] In a first aspect, the present application provides a negative electrode material, which includes graphite. The graphite surface has pores. In a circular area with a diameter of 1 μm on the graphite surface, the number of pores is 20 to 2000, and the average diameter of the pores is 10 nm to 100 nm; the negative electrode material contains metal elements, and the metal elements include at least one of Fe, Co, Ni, Cr, and Mn.

[0005] In the present application, the number of pores on the surface of graphite of the negative electrode material, the diameter of the pores, and the metal elements in the negative electrode material are regulated to form pores of uniform size on the surface of the graphite. When the negative electrode material is used in an electrochemical device, the lithium ions can improve the uniformity of lithium ion deposition during the lithium insertion process of the negative electrode material, and reduce lithium precipitation during fast charging; regulating the number and diameter of the pores can inhibit the nucleation and growth of lithium ions, form a nucleus-free and uniform lithium plating layer, inhibit the diffusion of lithium ions after nucleation and lithium precipitation on the surface of the negative electrode material, thereby improving the transmission efficiency of lithium ions, improving the room temperature kinetics and fast charging resistance of the negative electrode material, and combining with the metal elements doped in the negative electrode material, thereby further improving the kinetics of the negative electrode material, so as to further improve the kinetic performance of the electrochemical device. Moreover, when the negative electrode material is used in an electrochemical device, the graphite surface has a specific number of pores and an average diameter of the pores, which is beneficial to promote the reduction of anions in the electrolyte, so as to form a SEI film containing more inorganic components (such as LiF, Li2CO3). The inorganic components can improve the mechanical strength of the SEI film and inhibit the growth of lithium dendrites, thereby improving the cycle stability of the negative electrode material and further improving the cycle life of the electrochemical device.

[0006] Based on the first aspect, in some possible embodiments, the number of pores is 100 to 1000, and the average diameter of the pores is 20 nm to 50 nm, which can further improve the room temperature kinetics, fast charging resistance to lithium deposition and cycle stability of the negative electrode material, and improve the kinetic performance and cycle life of the electrochemical device.

[0007] Based on the first aspect, in some possible embodiments, based on the mass of the negative electrode material, the mass proportion of the metal element is 20 ppm to 400 ppm, which is beneficial to inhibit the nucleation growth of lithium ions, and can also help improve electronic conductivity, and improve the cycle stability and kinetic performance of the negative electrode material.

[0008] Based on the first aspect, in some possible implementations, in deionized water at pH = 7, the absolute value of the Zeta potential of the negative electrode material ZP ≥ 20 mV. This is beneficial to improve the dispersion uniformity and stability of the negative electrode material slurrying process, thereby improving the room temperature kinetics and cycle stability of the electrochemical device.

[0009] Based on the first aspect, in some possible embodiments, the pore volume of the negative electrode material is 0.003 cm 3 / g to 0.01cm 3 / g. It is beneficial to improve the electrolyte infiltration and lithium ion transfer rate, thereby improving the kinetic performance of the electrochemical device.

[0010] Based on the first aspect, in some possible implementations, the main pore size of the negative electrode material is 0.5 nm to 2 nm. Combined with the mesopores on the surface of the negative electrode material having an average pore size of 10 nm to 100 nm, the above pore structures work together to improve the kinetic performance of the electrochemical device.

[0011] Based on the first aspect, in some possible implementations, the particle sizes Dv50 and Dv99 of the negative electrode material satisfy: 2.0≤Dv99 / Dv50≤5.0; and both the energy density and cycle stability of the electrochemical device can be taken into account.

[0012] Based on the first aspect, in some possible implementations, the particle size Dv50 of the negative electrode material satisfies: 8 μm ≤ Dv50 ≤ 15 μm. This is beneficial to reduce the side reaction between the negative electrode material and the electrolyte, so as to improve the fast charging and anti-lithium deposition capability and cycle performance of the electrochemical device.

[0013] Based on the first aspect, in some possible implementations, the specific surface area of ​​the negative electrode material is 3m 2 / g to 10m 2 / g; it is beneficial to reduce the side reaction between the negative electrode material and the electrolyte, so that the electrochemical device has good cycle performance.

[0014] Based on the first aspect, in some possible embodiments, the tap density of the negative electrode material is 0.9 g / cm 3 Up to 1.0g / cm 3 The tap density within this range is beneficial to improving the energy density of the negative electrode material, and when the negative electrode material is used to prepare the slurry, it is also beneficial to reduce the amount of binder used and has good processing performance.

[0015] Based on the first aspect, in some possible implementations, the degree of graphitization of the negative electrode material is 92% to 96%, which can make the negative electrode material have a higher capacity and excellent kinetic performance, which is beneficial to improving the kinetic performance of the electrochemical device; The second aspect of the present application provides a method for preparing a negative electrode material, the preparation method comprising the following steps: dissolving an anionic surfactant in water, adding a metal salt compound, mixing evenly, and obtaining a treatment agent solution; adding a carbon material to the treatment agent solution, mixing evenly, and drying to obtain a powder; in an inert atmosphere, heat treating the powder, heating to 500°C to 600°C at 5°C / min to 30°C / min, and keeping warm for 3h to 6h to obtain an intermediate; acid washing the intermediate, washing it with water to neutrality, and drying to obtain a negative electrode material. In the above-mentioned preparation method, the anionic surfactant will form some negative charges, and the negative charges will form salts when combined with metal ions. The formed salts will decompose to form oxide nuclei during the subsequent heat treatment process, and by controlling the heating rate of the powder and the heat treatment temperature, the size of the oxide nucleation is regulated, so that the size of the average diameter of the pores can be changed. And through the synergistic effect of anionic surfactants and metal salt compounds on carbon materials, more evenly distributed pores are formed on the surface of the carbon material, and the number of pores in a specific area is regulated.

[0016] Based on the second aspect, in some possible embodiments, the metal salt compound accounts for 10% to 30% of the mass of the carbon material, which is conducive to promoting the metal salt compound to fully cooperate with the anionic surfactant to act on the carbon material to form uniform pores and a suitable average diameter of the pores on the surface of the carbon material.

[0017] Based on the second aspect, in some possible embodiments, the metal salt compound includes at least one of chlorides, nitrates, and sulfates of Fe, Co, Ni, Cr, and Mn; or / and the anionic surfactant includes at least one of sodium oleate, sodium lauryl sulfate, sodium lauryl ether sulfate, sodium stearate, and sodium myristic acid; or / and the carbon material is selected from at least one of artificial graphite, natural graphite, hard carbon, and soft carbon. The above-mentioned anionic surfactant will form some negative charges, and the negative charges will form salts when combined with metal ions. The formed salts will decompose to form oxide nuclei during the subsequent heat treatment process, and will generate pores in the carbon material after pickling, and will act on the carbon material in combination with the added metal salt compound to form more evenly distributed pores on the surface of the carbon material.

[0018] The third aspect of the present application provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet includes a negative electrode material. The electrochemical device including the negative electrode material can improve the kinetic performance and cycle life of the electrochemical device.

[0019] In a fourth aspect, the present application provides an electronic device, which includes an electrochemical device. The electrochemical device supplies power to a load in the electronic device, and the electrochemical device including the above-mentioned negative electrode material is conducive to improving the service life and fast charging performance of the electronic device. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 In the figure, (a) is a scanning electron microscope image of the negative electrode material in Example 1 of the present application; (b) is a local enlarged image of (a).

[0021] Figure 2 Graph showing the pore size distribution of the negative electrode materials in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0022] The technical scheme in the embodiment of the present application is described clearly and in detail below. Obviously, the described embodiment is a part of the embodiment of the present application, rather than all the embodiments. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.

[0023] The present application provides a negative electrode material and a preparation method thereof, an electrochemical device and an electronic device.

[0024] An embodiment of the present application provides an electrochemical device, which includes a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.

[0025] The shell can be a packaging bag encapsulated by a packaging film (such as an aluminum-plastic film), such as the electrochemical device is a soft-pack battery. In other embodiments, the electrochemical device can also be a steel shell battery, an aluminum shell battery, etc.

[0026] The electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet. The electrode assembly may be a laminated structure, which is formed by alternating the positive electrode sheet, the separator and the negative electrode sheet. In other embodiments, the electrode assembly may also be a wound structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet and then winding them.

[0027] Negative electrode The present application provides a negative electrode material, which includes graphite. The graphite surface has pores, and the number of pores in a circular area with a diameter of 1 μm on the graphite surface is 20 to 2000, and the average diameter of the pores is 10 nm to 100 nm; the negative electrode material also contains a metal element, and the metal element includes at least one of Fe, Co, Ni, Cr, and Mn.

[0028] In the present application, the number of pores on the surface of graphite of the negative electrode material, the diameter of the pores, and the metal elements in the negative electrode material are regulated to form pores of uniform size on the surface of the graphite. When the negative electrode material is used in an electrochemical device, the lithium ions can improve the uniformity of lithium ion deposition during the lithium insertion process of the negative electrode material, and reduce lithium precipitation during fast charging; regulating the number and diameter of the pores can inhibit the nucleation and growth of lithium ions, form a nucleus-free and uniform lithium plating layer, inhibit the diffusion of lithium ions after nucleation and lithium precipitation on the surface of the negative electrode material, thereby improving the transmission efficiency of lithium ions, improving the room temperature kinetics and fast charging resistance of the negative electrode material, and combining with the metal elements doped in the negative electrode material, thereby further improving the kinetics of the negative electrode material, so as to further improve the kinetic performance of the electrochemical device. Moreover, when the negative electrode material is used in an electrochemical device, the graphite surface has a specific number of pores and an average diameter of the pores, which is beneficial to promote the reduction of anions in the electrolyte, so as to form a SEI film containing more inorganic components (such as LiF, Li2CO3). The inorganic components can improve the mechanical strength of the SEI film and inhibit the growth of lithium dendrites, thereby improving the cycle stability of the negative electrode material and further improving the cycle life of the electrochemical device.

[0029] If the number of holes is small, such as less than 20, or the average diameter of the holes is small, such as less than 10nm, the effect on improving the uniformity of lithium ion deposition and forming a lithium plating layer is not obvious, which is not conducive to improving the room temperature kinetics and fast charging resistance to lithium precipitation of the negative electrode material; if the number of holes is large, such as greater than 2000, it may affect the structural stability of the negative electrode material and affect the cycle performance of the negative electrode material; if the average diameter of the holes is large, such as greater than 100nm, the effect on inhibiting the nucleation and growth of lithium ions is small, which will affect the room temperature kinetics and fast charging resistance to lithium precipitation of the negative electrode material.

[0030] In some embodiments, the number of holes in a circular area with a diameter of 1 μm on the graphite surface can be 20, 30, 50, 100, 200, 300, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1500, 1700, 1800, 1900, 2000 or any value in the range formed by any two of the above values. The average diameter of the holes can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm or any value in the range formed by any two of the above values.

[0031] In some embodiments, in a circular area with a diameter of 1 μm on the graphite surface, the number of pores is 100 to 1000, and the average diameter of the pores is 20 nm to 50 nm. This can further improve the room temperature kinetics, fast charging resistance to lithium deposition and cycle stability of the negative electrode material, and improve the kinetic performance and cycle life of the electrochemical device.

[0032] In some embodiments, based on the mass of the negative electrode material, the mass proportion of the metal element is 20ppm to 400ppm. The mass proportion of the metal element within the above range can be beneficial to improving electronic conductivity and improving the kinetic properties of the negative electrode material. The smaller the diameter of the gridded nano-sized pore structure, the more conducive it is to suppressing the thermodynamic process in the early stage of lithium metal nucleation, so that its lithium ion nucleation is limited, thereby forming a non-nuclear and uniform lithium plating layer, and improving the stability of the negative electrode material cycle. At the same time, a higher content of metal elements will also increase the main pore diameter of the graphite with a gridded nano-sized pore structure on the surface, which is not conducive to suppressing the nucleation growth of lithium ions. And containing a higher content of magnetic metal elements is not conducive to the stability of the battery cycle, so the content of metal elements in the negative electrode material should not be too high. In some embodiments, the mass percentage of the metal element can be 20ppm, 50ppm, 70ppm, 80ppm, 100ppm, 120ppm, 150ppm, 170ppm, 200ppm, 250ppm, 270ppm, 300ppm, 350ppm, 370ppm, 400ppm or any value within the range formed by any two of the above values.

[0033] In some embodiments, in deionized water at pH=7, the absolute value of the Zeta potential of the negative electrode material ZP≥20mV. The absolute value of the Zeta potential of the negative electrode material satisfies the above conditions, indicating that the surface of the negative electrode material has more hydrophilic groups such as -OH, and the surface with pores has good hydrophilicity, which is beneficial to improve the uniformity and stability of the dispersion of the negative electrode material during the slurrying process, thereby improving the room temperature kinetics and cycle stability of the electrochemical device. In some embodiments, the absolute value ZP of the Zeta potential of the negative electrode material can be 20mV, 21mV, 22mV, 24mV, 26mV, 27mV, 28mV, 29mV, 30mV, 31mV, 32mV, 34mV, 36mV, 38mV, 39mV, 40mV or any value within the range composed of any two of the above values.

[0034] In some embodiments, the pore volume of the negative electrode material is 0.003 cm 3 / g to 0.01cm 3 / g, within this range, it indicates that the negative electrode material has a porous structure, which is beneficial to improve electrolyte infiltration and lithium ion transmission rate, thereby improving the kinetic performance of the electrochemical device. In some embodiments, the pore volume of the negative electrode material can be 0.003cm 3 / g, 0.005cm 3 / g, 0.006cm 3 / g, 0.007cm 3 / g, 0.008cm 3 / g, 0.009cm 3 / g, 0.01cm 3 / g or any value within the range formed by any two of the above values.

[0035] In some embodiments, the main pore diameter of the negative electrode material is between 0.5 nm and 2 nm. Within this range, it can be ensured that the main contribution to the pore volume of the negative electrode material comes from micropores with a pore diameter of 0.5 nm to 2 nm, combined with the mesopores with an average pore diameter of 10 nm to 100 nm on the surface of the negative electrode material. The above pore structures work together to improve the kinetic performance of the electrochemical device.

[0036] In some embodiments, the particle sizes Dv50 and Dv99 of the negative electrode material satisfy: 2.0≤Dv99 / Dv50≤5.0, and the particle sizes Dv50 and Dv99 of the negative electrode material satisfy the above relationship, which can take into account both the energy density and cycle stability of the electrochemical device. Dv99 / Dv50 can be 2, 2.5, 3, 3.5, 4, 4.5, 5 or any value within the range of any two of the above values.

[0037] In some embodiments, the particle size Dv50 of the negative electrode material satisfies: 8 μm ≤ Dv50 ≤ 15 μm. This is beneficial to reduce the side reaction between the negative electrode material and the electrolyte, so as to improve the fast charging and anti-lithium deposition ability and cycle performance of the electrochemical device. V 50 is also called "median particle size", which means that in the particle size distribution of the negative electrode material particles, the particle size measured from the small particle size reaches 50% of the cumulative volume, that is, the volume of the negative electrode material particles smaller than this particle size accounts for 50% of the total volume of the negative electrode material particles. In some embodiments, the particle size Dv50 of the negative electrode material can be 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or any value within the range formed by any two of the above values.

[0038] In some embodiments, the specific surface area of ​​the negative electrode material is 3 m 2 / g to 10m 2 / g; The specific surface area of ​​the negative electrode material is within the above range, which is conducive to reducing the side reaction between the negative electrode material and the electrolyte, so that the electrochemical device has good cycle performance. In some embodiments, the specific surface area of ​​the negative electrode material can be 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g or any value within the range formed by any two of the above values.

[0039] In some embodiments, the tap density of the negative electrode material is 0.9 g / cm 3 Up to 1.0g / cm 3 The tap density within this range is conducive to improving the energy density of the negative electrode material, and when the negative electrode material is used to prepare the slurry, it is also conducive to reducing the amount of binder used, and the processing performance is good. In some embodiments, the tap density of the negative electrode material can be 0.9 g / cm 3 、0.93g / cm 3 , 0.95g / cm 3 , 0.96g / cm 3 、0.98g / cm 3 , 1g / cm 3 Or any value within the range formed by any two of the above values.

[0040] In some embodiments, the degree of graphitization of the negative electrode material is 92% to 96%. When the degree of graphitization of the negative electrode material is within the above range, the negative electrode material can have a higher capacity and excellent kinetic performance, which is beneficial to improving the kinetic performance of the electrochemical device; and when the degree of graphitization of the negative electrode material is within the above range, the performance of graphite can be fully exerted. In some embodiments, the degree of graphitization of the negative electrode material can be 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96% or any value within the range formed by any two of the above values.

[0041] The present application also provides a method for preparing a negative electrode material, the preparation method comprising the following steps: S1. dissolving anionic surfactant in water, adding metal salt compound, and mixing evenly to obtain treatment agent solution, wherein the mass ratio of anionic surfactant to metal salt compound is 1:1 to 3:1.

[0042] In some embodiments, the metal salt compound includes at least one of chlorides, nitrates, and sulfates of Fe, Co, Ni, Cr, and Mn; such as ferric chloride hexahydrate, cobalt chloride, cobalt nitrate, and the like.

[0043] The anionic surfactant includes at least one of sodium oleate, sodium lauryl sulfate, sodium lauryl ether sulfate, sodium stearate, and sodium myristic acid.

[0044] In the treating agent solution, the anionic surfactant will form some negative charges, and the negative charges will combine with metal ions to form salts. The formed salts will decompose to form oxide crystal nuclei during the subsequent heat treatment process, and will produce pores in the carbon material after acid washing. The added metal salt compounds will act on the carbon material to form more evenly distributed pores on the surface of the carbon material.

[0045] In some embodiments, the mass ratio of the anionic surfactant to the metal salt compound can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1 or any value within the range formed by any two of the above values.

[0046] In some embodiments, the treatment agent solution is also subjected to heat treatment, the heating temperature is 80-100°C, and the heating time is 1h-2h. The heating treatment can be performed in an oil bath. In some embodiments, the heating temperature can be 80°C, 85°C, 90°C, 95°C, 100°C, or any value within the range formed by any two of the above values, and the heating time can be 1h, 1.2h, 1.5h, 1.8h, 2h, or any value within the range formed by any two of the above values. After the treatment agent is heated, it can promote the full dissolution of the metal salt compound to improve the uniformity of the metal salt compound.

[0047] S2. Add the carbon material to the treatment agent solution, mix evenly, and dry to obtain powder.

[0048] The metal salt compound accounts for 10% to 30% of the mass of the carbon material. The mass ratio of the metal salt compound within the above range is conducive to promoting the metal salt compound to fully cooperate with the anionic surfactant to act on the carbon material to form uniform pores and a suitable average diameter of the pores on the surface of the carbon material. In some embodiments, the mass ratio of the metal salt compound to the carbon material can be 10%, 15%, 18%, 20%, 23%, 25%, 28%, 30% or any value within the range formed by any two of the above values.

[0049] The carbon material is selected from at least one of artificial graphite, natural graphite, hard carbon and soft carbon. Artificial graphite and natural graphite can improve the lithium ion transmission performance of the negative electrode material, so that the electrochemical device can obtain better charging performance and even better cycle performance under the premise of having a higher energy density. Hard carbon and soft carbon can increase the charge and discharge capacity or cycle life of the negative electrode material and increase the cycle life of the electrochemical device.

[0050] S3. In an inert atmosphere, the powder is heat treated, the temperature is increased to 500°C to 600°C at 5°C / min to 30°C / min, and the temperature is kept for 3h to 6h to obtain an intermediate.

[0051] In some embodiments, the inert atmosphere can be nitrogen or argon.

[0052] In some embodiments, in an inert atmosphere, the powder is heated to 500°C to 600°C at 5°C / min to 30°C / min, and the holding time is 3h to 6h. The heating rate of the powder can be 5°C / min, 10°C / min, 15°C / min, 20°C / min, 25°C / min, 30°C / min, or any value within the range of any two of the above values. The temperature of the powder treatment is 500°C, 530°C, 550°C, 580°C or 600°C, or any value within the range of any two of the above values. The holding time can be 3h, 4h, 5h, 6h, or any value within the range of any two of the above values.

[0053] S4. The intermediate is subjected to acid washing, washed with water until neutral, and dried to obtain the negative electrode material.

[0054] In some embodiments, the concentration of the pickling is 0.5 mol / L to 3 mol / L, and the concentration of the pickling can be 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, or any value within the range formed by any two of the above values. The acid used for pickling can be dilute hydrochloric acid or dilute nitric acid.

[0055] In some embodiments, before the intermediate is washed with water, the intermediate is heated to 80° C. to 100° C. and stirred for 3 h to 6 h to dissolve the metal in the intermediate in the solution for easy washing.

[0056] In the above preparation method, the anionic surfactant will form some negative charges, and the negative charges will combine with metal ions to form salts. The formed salts will decompose to form oxide nuclei during the subsequent heat treatment process, and by controlling the heating rate of the powder and the heat treatment temperature in step S3, the size of the oxide nucleation is regulated, so that the size of the average diameter of the pores can be changed. And through the synergistic effect of anionic surfactants and metal salt compounds on carbon materials, more evenly distributed pores are formed on the surface of the carbon material, and the number of pores in a specific area is regulated. And in the preparation method provided in the present application, by regulating the thermal decomposition process, the metal nano-oxide in the powder is uniformly nucleated on the graphite surface to form a more regular nano-sized pore structure, and then the metal oxide is etched away by an acid solution to obtain a negative electrode material with a more evenly distributed grid nano-sized pore structure.

[0057] Isolation film The material and shape of the separator used in the electrochemical device of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0058] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.

[0059] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly (vinylidene fluoride-hexafluoropropylene).

[0060] Electrolyte According to some embodiments of the present application, the electrolyte includes an organic solvent, a lithium salt and an optional additive. The organic solvent in the electrolyte of the present application may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The electrolyte used in the electrolyte according to the present application is not limited, and it can be any electrolyte known in the prior art. The additive of the electrolyte according to the present application may be any additive known in the prior art that can be used as an electrolyte additive. In some embodiments, the organic solvent includes, but is not limited to: ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate or ethyl propionate. In some embodiments, the organic solvent includes an ether solvent, for example, including at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME). In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB), or lithium di(oxalatoborate) LiBF2(C2O4) (LiDFOB). In some embodiments, the additive includes at least one of fluoroethylene carbonate and adiponitrile.

[0061] Positive electrode The positive electrode plate includes a positive current collector and a positive active layer disposed on the positive current collector. The positive current collector may be aluminum foil or nickel foil, etc., or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and the polymer substrate. The positive active layer contains a positive active material, and the positive active material includes a compound that reversibly embeds and deintercalates lithium ions (i.e., a lithiated intercalation compound). In some embodiments, the positive active material may include a lithium transition metal composite oxide. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive active material may include but is not limited to at least one of lithium cobaltate, lithium nickel manganese cobaltate, lithium nickel manganese aluminum, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide and lithium titanate.

[0062] The positive electrode active layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode active layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc. At least one of the above.

[0063] The positive electrode active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0064] The electrochemical device is applied to an electronic device to power the load in the electronic device. Moreover, the negative electrode material in the electrochemical device has excellent kinetics, fast charging anti-lithium deposition ability and cycle stability, which is beneficial to improve the service life and fast charging performance of the electronic device. Among them, the electronic device may include but is not limited to a laptop computer, a pen input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini CD, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium ion capacitor, etc.

[0065] The present application is described below by specific examples and comparative examples. Those skilled in the art should understand that the preparation methods described in the present application are only examples, and any other suitable preparation methods are within the scope of the present application.

[0066] Example 1 <Preparation of negative electrode materials> 1. Dissolve 300g of sodium oleate evenly in 3L of water, add 100g of ferric chloride hexahydrate powder, and stir in an oil bath at 80°C for 2h to obtain a treatment agent solution.

[0067] 2. Slowly add 1 kg of graphite powder to the treating agent solution while stirring to evenly mix it with the graphite powder. Stir in an oil bath at 80°C for 6 hours and then transfer to an oven for drying to obtain a powder.

[0068] 3. The above powder was transferred into a box furnace for heat treatment, and the temperature was raised to 500°C at 20°C / min under an inert atmosphere, and kept at this temperature for 3h to obtain an intermediate, i.e., treated graphite.

[0069] 4. Add the treated graphite to a 3 mol / L hydrochloric acid solution, stir in an oil bath at 80°C for 6 h, wash with water until neutral, and dry to obtain the negative electrode material.

[0070] The above-mentioned negative electrode material, thickener sodium carboxymethyl cellulose (CMC-Na), and binder styrene-butadiene rubber (SBR) were mixed in a weight ratio of 95:2:3, and deionized water was added, and the mixture was stirred and mixed evenly to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry was 75wt%; the negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided coating of a negative electrode material layer with a coating thickness of 80μm. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer coated on both sides. Dry under vacuum conditions at 120°C for 1 hour, and then obtain a negative electrode sheet with a specification of 78mm×875mm after cold pressing, cutting, and slitting.

[0071] <Preparation of positive electrode sheet> The positive electrode active material lithium cobalt oxide (LiCoO2), the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) were mixed in a weight ratio of 96:2:2, and N-methylpyrrolidone (NMP) was added and stirred to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry was 70wt%; the positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 120℃ for 1 hour to obtain a positive electrode sheet with a single-sided positive electrode material layer coated with a thickness of 60μm. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer. Dry under vacuum conditions at 120℃ for 1 hour, and then after cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 74mm×867mm was obtained.

[0072] <Preparation of Electrolyte> In an argon atmosphere glove box with a water content of less than 10ppm, non-aqueous organic solvents ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) were mixed at a weight ratio of 1:1:1, and then lithium salt lithium hexafluorophosphate (LiPF6) was added and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12.5%, and the balance is non-aqueous organic solvent.

[0073] <Preparation of Separator Film> A polypropylene / polyethylene composite film with a thickness of 7 μm was used as the isolation membrane.

[0074] <Preparation of lithium-ion batteries> The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly. After welding the pole ears, the electrode assembly is placed in an aluminum-plastic film packaging bag, and after drying, the electrolyte is injected, and the lithium-ion battery is obtained through vacuum packaging, standing, forming (forming upper limit voltage is 4.5V, forming temperature is 70°C, and forming standing time is 2 hours), degassing, trimming and other processes.

[0075] Example 2 The difference between Example 2 and Example 1 is that, except for the heat treatment heating rate of 25°C / min in the preparation of the negative electrode material - step 3, the remaining steps are the same as those in Example 1.

[0076] Example 3 The difference between Example 3 and Example 1 is that, except for the heat treatment heating rate of 10°C / min in the preparation of the negative electrode material - step 3, the remaining steps are the same as Example 1.

[0077] Example 4 The difference between Example 4 and Example 1 is that, except for the heat treatment heating rate of 30°C / min in the preparation of the negative electrode material, the remaining steps are the same as those in Example 1.

[0078] Example 5 The difference between Example 5 and Example 1 is that in the preparation of the negative electrode material-step 1, 200g of ferric chloride hexahydrate is added to water; and in the preparation of the negative electrode material-step 3, the heat treatment heating rate is 5°C / min, and the remaining steps are the same as Example 1.

[0079] Example 6 The difference between Example 6 and Example 3 is that, in the preparation of the negative electrode material-step 1, "100g of ferric chloride hexahydrate" is replaced by "150g of nickel nitrate hexahydrate", and in the preparation of the negative electrode material-step 3, "500°C, keep warm for 3h" is replaced by "600°C, keep warm for 3h", and the remaining steps are the same as Example 3.

[0080] Example 7 The difference between Example 7 and Example 3 is that, except for replacing "100g ferric chloride hexahydrate" with "150g chromium trichloride hexahydrate" in the preparation of negative electrode materials-step 1, and replacing "500°C, keep warm for 3h" with "600°C, keep warm for 3h" in the preparation of negative electrode materials-step 3, the remaining steps are the same as Example 3.

[0081] Example 8 The difference between Example 8 and Example 3 is that, except for replacing "100g ferric chloride hexahydrate" with "300g manganese chloride tetrahydrate" in the preparation of negative electrode materials-step 1, and replacing "500°C, keep warm for 3h" with "600°C, keep warm for 3h" in the preparation of negative electrode materials-step 3, the remaining steps are the same as Example 3.

[0082] Comparative Example 1 Only the graphite raw material in the negative electrode material preparation step 2 is used as the negative electrode material without any other processing.

[0083] Comparative Example 2 Except that in negative electrode material preparation - step 3, the heat treatment heating rate is changed to 35°C / min, the remaining steps are the same as those in Example 1.

[0084] Comparative Example 3 Except that in the negative electrode material preparation-step 1, 350g of ferric chloride hexahydrate is added to water; and in the negative electrode material preparation-step 3, the heat treatment heating rate is 2°C / min, the remaining steps are the same as Example 1.

[0085] The negative electrode materials prepared in various embodiments and comparative examples and the assembled lithium-ion batteries were tested.

[0086] Test method: Negative electrode material to be tested: Take a fully discharged lithium-ion battery, disassemble it, take out the negative electrode, soak it in ethylene carbonate (DMC) for 20 minutes, then rinse it with DMC and acetone in turn to remove the electrolyte and the surface solid electrolyte interface (SEI) film, then place it in an oven and bake it at 80℃ for 12h to obtain the treated negative electrode sheet. Use a scraper to scrape off the negative electrode material layer on the negative electrode sheet, and heat treat the scraped negative electrode material layer powder in a tube furnace at 350℃ for 4h under argon protection to obtain the negative electrode material.

[0087] Test of the number of holes and the average diameter of the holes: Using a scanning electron microscope model ZEIS-SEM (Sigma-02-33), the negative electrode material dispersed in ethanol is pasted on the sample stage with conductive glue, the sample stage is installed in the sample chamber and ensured to be fixed, and the sample chamber is closed. Turn on the vacuum pump, set the following parameters: acceleration voltage is 10kV, aperture is 30μm, working distance is 2mm to 9mm, current is 2.335A, and start the test after determining the parameters. Turn on the high voltage, focus, magnify 30000 times, and shoot the negative electrode material. Select the negative electrode material particles in the field of view, and the number of holes and the average diameter of the holes in any circular area with a diameter of 1μm can be obtained through image analysis software. Test the number of holes in 10 areas (circular areas with a diameter of 1μm), calculate the average value, and you can get the number of holes in the circular area with a diameter of 1μm on the graphite surface. The diameter of the holes on the surface within a single circular area with a diameter of 1 μm (the diameter of the hole refers to the distance between the two farthest points on the circumference of the hole), and the average diameter of the holes on the surface within a single area is obtained, and then 10 areas (circular areas of 1 μm) are tested to finally obtain the average diameter of the holes on the calculated surface.

[0088] Metal element content test: Microwave digestion method and PEICP-OESOptima7000DV were used to test the mass percentage content of metal elements in the negative electrode material.

[0089] Pore ​​size distribution test: The pore size distribution test of the negative electrode material was carried out in an Ar atmosphere using an iPore620 specific surface and pore size analyzer, referring to GB / T21650.3-2011 "Determination of pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method Part 3: Analysis of micropores by gas adsorption method" to obtain the pore volume and main pore size of the negative electrode material. The main pore size refers to the pore diameter with the highest pore volume peak in the pore volume distribution diagram.

[0090] Zeta potential test: The negative electrode material powder was prepared into a deionized water solution with a concentration of 0.0025 g / mL using a Malvern particle size analyzer Nano-ZS. The Zeta potential was tested three times and the average value was taken to obtain the absolute value ZP of the Zeta potential of the negative electrode material.

[0091] Particle size test: The particle size of the negative electrode material particles was measured using a Malvern particle size tester (model: MasterSizer2000). 0.02 g of negative electrode material particles were added to a 50 mL clean beaker, and 20 mL of dispersant ethanol was added. Ultrasonic cleaning was performed in a 120 W ultrasonic cleaning machine for 30 minutes to completely disperse the negative electrode material particles in ethanol to obtain a sample dispersion. The sample dispersion was tested using a Malvern particle size tester to obtain the particle sizes Dv50 and Dv99 of the negative electrode material particles.

[0092] Specific surface area (SSA) test: In accordance with the national standard "Determination of the specific surface area of ​​solid substances by gas adsorption BET method" (GB / T19587-2017), the specific surface area of ​​the negative electrode material was tested by nitrogen adsorption method using a specific surface area analyzer (model TristarⅡ3020M).

[0093] Tap density TD test: In accordance with the national standard GB / T24533-2019, a density analyzer (model GeoPyc1365) was used to test the tap density TD of the negative electrode material.

[0094] Graphitization degree test: The negative electrode material was tested by X-ray powder diffractometer (XRD, instrument model: BrukerD8ADVANCE), with CuKα as the target material; the voltage and current were 40KV / 40mA, the scanning angle range was 5˚ to 80˚, the scanning step length was 0.00836˚, and the time per step was 0.3s. At the same time, 15% silicon powder was added, and according to the principle of internal standard method, the peak position of silicon standard was used to calibrate the instrument and test error, so as to accurately calculate the characteristic peak position of graphite negative electrode material and obtain the graphitization degree of graphite negative electrode material.

[0095] Lithium-ion battery charging rate performance test: The lithium-ion battery is repeatedly charged and discharged through the following steps, and the capacity of each charging stage is counted to calculate the capacity ratio of the constant current charging (CC) stage. The specific steps are: First, place the lithium-ion battery in a 25°C environment for 6 hours. The lithium-ion battery is charged with constant current at a charging rate of 1C. After constant current charging to 4.48V, it is switched to constant voltage charging (CV). Charging is stopped when the charging current is lower than 0.05C. The above charging mode is the CC+CV charging mode, and then it is set aside for 5 minutes. Then discharge to 3V at a constant current of 0.2C and set aside for 5 minutes to ensure the integrity of the subsequent charging and discharging process. Then charge the lithium-ion battery at a charging rate of 3C according to the aforementioned CC+CV charging mode, and calculate the capacity ratio of the CC stage at a charging rate of 3C. The calculation formula is as follows: The capacity ratio of the CC stage at the 3C charging rate = [the charging capacity of the CC stage at the 3C charging rate / the total charging capacity (CC+CV) at the 3C charging rate] × 100%.

[0096] Five lithium-ion batteries of each comparative example and embodiment were taken for testing, and the average value of the capacity percentage of the CC stage at five 3C charging rates was taken as the final result.

[0097] In the present application, the higher the capacity proportion of the CC stage under the 3C charging rate of the lithium-ion battery, the larger the capacity of the lithium-ion battery charged at a large rate, and the smaller the polarization of the lithium-ion battery, indicating that the charging rate performance of the lithium-ion battery is better; the lower the capacity proportion of the CC stage under the 3C charging rate of the lithium-ion battery, the smaller the capacity of the lithium-ion battery charged at a large rate, and the larger the polarization of the lithium-ion battery, indicating that the charging rate performance of the lithium-ion battery is worse.

[0098] Lithium-ion battery 3C cycle capacity retention test: In an environment of 25°C, the lithium ion battery is charged and discharged for the first time, and constant current and constant voltage charging is performed at a charging current of 3C until the upper limit voltage is 4.48V, and then constant current discharge is performed at a discharge current of 1C, and the discharge cut-off voltage is 3V, and the discharge capacity A of the lithium ion battery is measured; then, 1000 charging and discharging cycles are performed according to the above steps in an environment of 0°C, and the 1000th lithium ion battery discharge capacity B is measured, then the lithium ion battery 3C cycle capacity retention rate = B / A×100%; 5 lithium ion batteries of each comparative example and embodiment are taken, and the average value is taken as the final result.

[0099] Table 1 Table 2 See also Figure 1 The surface of the negative electrode material prepared in Example 1 forms a grid-like nano-sized pore structure. In (a) and (b), the surface of the negative electrode material has a relatively uniform and orderly arranged grid-like nano-sized pore structure. Figure 2 , Figure 2 In the pore size distribution curve diagram of the negative electrode materials in Example 1 and Comparative Example 1, the pore volume of the negative electrode material prepared in Example 1 is significantly larger than the pore volume of the negative electrode material prepared in Comparative Example 1.

[0100] According to Examples 1 to 5 and Comparative Examples 2 and 3, it can be seen that different heating rates have a direct impact on the average diameter of the final pores. The higher the heating rate, the smaller the average diameter of the pores, and vice versa. This is because the metal nanooxide is decomposed from the salt formed by the metal salt and the anionic surfactant, and when the critical saturation is exceeded, the crystal nucleus particles are formed; these crystal nucleus particles continue to increase during the growth stage until all the metal salts are consumed. The monomer concentration formed at a low heating rate only touches the critical supersaturation, thereby forming a smaller number of crystal nuclei, resulting in a larger final grain size. A high heating rate will form more crystal nucleus particles, resulting in a smaller grain size, and ultimately a smaller pore diameter.

[0101] Compared with Comparative Example 1, the negative electrode materials prepared in Examples 1 to 8 have improved ZP potentials after being treated with a surface meshed nano-sized pore structure. This is because after the negative electrode material is treated, hydrophilic groups such as -OH are added to the graphite surface, making the graphite with a meshed nano-sized pore structure on the surface have good hydrophilicity, which is beneficial to its dispersion uniformity and stability in the slurry.

[0102] Compared with Comparative Examples 2 and 3, the larger the average diameter of the surface pores of the negative electrode materials prepared in Examples 1 to 8, the greater the element content in the negative electrode materials. The higher the magnetic metal elements, the greater the stability of the battery cycle, so the element content should not be too high. At the same time, a higher element content will also increase the main pore diameter of the surface pore structure. It is generally believed that the average diameter of the gridded nano-sized pore structure is between 10nm and 100nm, preferably, the average diameter is between 20nm and 50nm, which is more conducive to suppressing the thermodynamic process of the initial nucleation of lithium metal, so that its nucleation is limited, thereby forming a non-nuclear uniform lithium plating layer, and promoting the stability of the cycle. In addition, the number of holes is between 20 and 2000, preferably, the number of holes is between 100 and 1000, which can improve the kinetic performance of the electrochemical device within the diameter range of the corresponding holes, while having excellent cycle stability.

[0103] In Table 2, the diameter of the pore structure in Example 1 is moderate, with an average diameter of 30 nm, and the capacity of the CC segment at a 3C charge rate accounts for a high proportion, indicating that the pore diameter within the preferred range is conducive to the improvement of kinetic performance at a high rate. At the same time, because it can inhibit the process of lithium nucleation, Example 1 also has an excellent cycle retention rate at a 3C charge rate.

[0104] The above disclosure is only a preferred implementation mode of the present application, and certainly cannot be used to limit the present application. Therefore, equivalent changes made according to the present application are still within the scope covered by the present application.

Claims

1. A negative electrode material, characterized in that: Comprising graphite, wherein the graphite surface has pores, within a circular region with a diameter of 1 μm on the graphite surface, the number of the pores is 20 to 2000, and the average diameter of the pores is 10 nm to 100 nm; The negative electrode material contains metal elements, and the metal elements include at least one of Fe, Co, Ni, Cr, and Mn.

2. The negative electrode material according to claim 1, characterized in that Based on the mass of the negative electrode material, the mass proportion of the metal element is 20 ppm to 400 ppm.

3. The negative electrode material according to claim 1, characterized in that In deionized water at pH=7, the absolute value of the Zeta potential ZP of the negative electrode material is ≥20 mV.

4. The negative electrode material according to any one of claims 1 to 3, characterized in that The negative electrode material satisfies at least one of the following conditions: (1) The pore volume of the negative electrode material is 0.003 cm 3 / g to 0.01cm 3 / g; (2) The main pore size of the negative electrode material is between 0.5 nm and 2 nm; (3) The number of the pores is between 100 and 1000, and the average diameter of the pores is between 20 nm and 50 nm.

5. The negative electrode material according to any one of claims 1 to 3, characterized in that The negative electrode material satisfies at least one of the following conditions: (1) The specific surface area of ​​the negative electrode material is 3m 2 / g to 10m 2 / g; (2) The tap density of the negative electrode material is 0.9 g / cm 3 Up to 1.0g / cm 3 ; (3) The graphitization degree of the negative electrode material is 92% to 96%; (4) The particle sizes Dv50 and Dv99 of the negative electrode material satisfy: 2.0≤Dv99 / Dv50≤5.0; (5) The particle size Dv50 of the negative electrode material satisfies: 8 μm ≤ Dv50 ≤ 15 μm.

6. A method for preparing a negative electrode material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Dissolving anionic surfactant in water, adding metal salt compound, and mixing evenly to obtain treatment agent solution; Adding the carbon material to the treatment agent solution, mixing evenly, and drying to obtain a powder; In an inert atmosphere, heat-treating the powder, raising the temperature to 500°C to 600°C at 5°C / min to 30°C / min, and keeping the temperature for 3h to 6h to obtain an intermediate; The intermediate is subjected to acid washing, washed with water until neutral, and dried to obtain the negative electrode material.

7. The preparation method according to claim 6, characterized in that The metal salt compound accounts for 10% to 30% by mass of the carbon material.

8. The preparation method according to claim 6 or 7, characterized in that: The metal salt compound includes at least one of chlorides, nitrates and sulfates of Fe, Co, Ni, Cr and Mn; or / and The anionic surfactant includes at least one of sodium oleate, sodium lauryl sulfate, sodium lauryl ether sulfate, sodium stearate, and sodium myristic acid; or / and The carbon material is selected from at least one of artificial graphite, natural graphite, hard carbon and soft carbon.

9. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises the negative electrode material according to any one of claims 1 to 5 or the negative electrode material prepared by the preparation method according to any one of claims 6 to 8.

10. An electronic device, characterized in that: The electronic device comprises the electrochemical device according to claim 9.

Citation Information

Patent Citations

  • Negative electrode material, and electrochemical device and electronic equipment comprising same

    CN113086978A

  • Graphite material and preparation method thereof, negative electrode material and lithium ion battery

    CN117963906A

  • Graphite material, carbon material for battery electrode, and battery

    US20140335428A1

  • Negative electrode material, electrochemical apparatus, and electronic apparatus

    WO2022266798A1